1987
DOI: 10.1029/jb092ib12p12587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moisture and carbon dioxide on concentrations of helium in soils and soil gases

Abstract: Helium is often measured in exploration programs, either in interstitial soil gases collected by hollow probe or in gases desorbed from pore spaces of soil samples. However, measured helium concentrations are affected by various parameters that must be considered when interpreting data, including the variation in concentration of other soil gases. The effects of moisture and carbon dioxide in the soil are particularly important. This study compares helium concentrations with soil moisture and carbon dioxide co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…1d). The soil gas survey was performed during the dry season, in order to provide stable meteorological conditions and minimal soil gas variation due to soil humidity (Hinkle and Ryder, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…1d). The soil gas survey was performed during the dry season, in order to provide stable meteorological conditions and minimal soil gas variation due to soil humidity (Hinkle and Ryder, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Only 3% of the data among those surveyed had a soil gas concentration higher than the allowed level prescribed by the UNSCEAR [42]. Radon in soil gas concentration can be influenced by many environmental factors, the most important among these factors being air temperature, barometric pressure, rainfall and snowfall on the radon signal acquired to possibly filter them out [40,[43][44][45]. In the other hand, radon release from soils and rocks is complex because in rock, uranium fixed in minerals along grain boundaries and in defects is susceptible to leaching, thus releasing radon trapped therein.…”
Section: Radon In Soil Gas Concentration Geogenic Radon Potential And...mentioning
confidence: 99%
“…Therefore, these uncertainties are sometimes so strong that they often weaken, even mask the nearsurface geochemical anomalies formed directly or indirectly by the hydrocarbons migrating from subsurface oil and gas reservoirs (Wu Xueming and Zhao Wenxian, 1995;Liu Xiaoyan et al, 2006). The previous research suggested that increases in soil moisture might lead to decreases in the concentrations of light hydrocarbons (Hinkle and Ryder, 1987). In addition, upward migration of gaseous hydrocarbons from subsurface oil and gas reservoirs is not strictly vertical (Xie Xuejing, 1992), but follows complicated pathways of faults, fractures, bedding planes, unconformities, or undiscovered microfissures (Jones and Drozd, 1983).…”
Section: Introductionmentioning
confidence: 98%